2021
DOI: 10.3389/fbioe.2020.620629
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Containing Alloy as Immunoregulatory Material in Bone Regeneration via Mitochondrial Oxidative Stress

Abstract: In the mammalian skeletal system, osteogenesis and angiogenesis are closely linked by type H vessels during bone regeneration and repair. Our previous studies confirmed the promotion of these processes by copper-containing metal (CCM) in vitro and in vivo. However, whether and how the coupling of angiogenesis and osteogenesis participates in the promotion of bone regeneration by CCM in vivo is unknown. In this study, M2a macrophages but not M2c macrophages were shown to be immunoregulated by CCM. A CCM, 316L−5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Applying a biomimetic polysaccharide hydrogel-metal scaffold composite loaded with IL-4 and BMP-2 within femoral defects in rats, Wang et al observed an increase in the number of M2 macrophages and in the proliferation and differentiation of skeletal progenitors into osteoblasts, which significantly improved bone regeneration (69). In another study, Xu et al (70) developed an intramedullary nail composed of a copper-containing stainless steel as a strategy to deliver copper ions at the injury site, as this ion had been previously shown to considerably induce M2 macrophage polarization in vitro (71). Using the drill-hole injury model in the tibia of mice, the authors reported an accelerated formation of new cortical bone in the animals that received the copper-enriched intramedullary nail.…”
Section: Perspectives For the Development Of Advanced Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying a biomimetic polysaccharide hydrogel-metal scaffold composite loaded with IL-4 and BMP-2 within femoral defects in rats, Wang et al observed an increase in the number of M2 macrophages and in the proliferation and differentiation of skeletal progenitors into osteoblasts, which significantly improved bone regeneration (69). In another study, Xu et al (70) developed an intramedullary nail composed of a copper-containing stainless steel as a strategy to deliver copper ions at the injury site, as this ion had been previously shown to considerably induce M2 macrophage polarization in vitro (71). Using the drill-hole injury model in the tibia of mice, the authors reported an accelerated formation of new cortical bone in the animals that received the copper-enriched intramedullary nail.…”
Section: Perspectives For the Development Of Advanced Therapiesmentioning
confidence: 99%
“…Using the drill-hole injury model in the tibia of mice, the authors reported an accelerated formation of new cortical bone in the animals that received the copper-enriched intramedullary nail. When the callus was evaluated, it was observed an increased infiltration of CD206 + M2a macrophages, which located close to the newly formed type-H vessels and around the surface of the neoformed osseous tissue (70).…”
Section: Perspectives For the Development Of Advanced Therapiesmentioning
confidence: 99%
“…M2 macrophages can produce regenerative factors such as osteogenic and angiogenic molecules, thus promoting neobone formation and revascularization [ 22 ]. CD206-expressing macrophages (M2a) express abundant platelet-derived growth factor type BB and promote the formation of blood vessels [ 49 ]. CD163-expressing macrophages (M2c) secrete high levels of matrix metalloproteinases 9 (MMP9) to promote vascular remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…During the early stages after implantation of biomaterials, the macrophages migrate to the implant area and differentiate into the pro-inflammatory M1 phenotype (classical type), triggering the defensive inflammation by the release of pro-inflammatory molecules, such as interleukin (IL)-1, tumor necrosis factor (TNF)-α and inducible nitric oxide synthase (iNOS) (Wu et al, 2020). The phenotype plasticity allows macrophages to switch into different phenotypes in response to distinct material signals (Miron and Bosshardt, 2016;Xu et al, 2020). Subsequently, antiinflammatory M2 macrophages (alternative type) participate in bone reconstruction by the production of antiinflammatory molecules, including arginase-1 (Arg-1), IL-10, and IL-4 (Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%